Edukasi Kesehatan Lingkungan Dan Pengelolaan Sampah Rumah Tangga Berbasis Komunitas Di Kelurahan Bugih - Fetty Nuritasari; Ema Surahmi; Royyan Julian; Kasanova, Ria (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Household waste management is a major challenge for cities in Indonesia, including Bugih Subdistrict, which has experienced an increase in waste generation in line with population growth and lifestyle changes. This issue is not merely a matter of cleanliness, but is directly related to environmental health and the quality of life of the community. This study aims to describe and evaluate the implementation of a community service programme in the form of education, facilitation, and assistance in community-based waste management in Bugih Village. A participatory approach was used, involving village officials, neighbourhood associations, family welfare organisations, youth organisations, and residents as the main actors. The intervention focused on improving environmental literacy, household waste sorting practices, small-scale composting, and the use of eco-bricks as educational tools. The results showed a significant increase in awareness and waste sorting practices, as measured through pre- and post-surveys and field observations. Active community participation proved to be a key factor in the success of the programme, reinforced by facilitation in the form of providing clearly labelled sorting areas and technical demonstration sessions. The existence of local waste banks also served as an economic incentive and ensured the integration of sorted waste into the recycling chain. The programme evaluation confirmed that the combination of education, facilitation, and behavioural nudges had a positive impact, although challenges such as limited facilities and behavioural consistency still need to be addressed. Conceptually, these findings reinforce the literature on the effectiveness of community-based approaches to waste management and provide practical recommendations for replication in other urban areas. The programme in Bugih Subdistrict contributes to the achievement of the national zero waste–zero emission 2050 agenda, while strengthening local capacity to create a healthier and more sustainable environment.